Historia de la micología médica en Colombia, 1930-1970 (2013)
ABSTRACT: The overall objective of this research was to understand the events that made possible the creation, diffusion and appropriation of medical mycology in Colombia between 1930 and 1970. It was based on the review of scientific journals and theses in different libraries, archives and documentation centers in Medellin and Bogota. The report includes the different problems faced by physicians and laboratory personnel concerning the classification of fungi, the relationship between dermatology and mycology, the development of the study of systemic mycoses and the role played by some persons in the institutionalization of medical mycology.